KAJIAN ROMANTISME PADA NOVEL GEEZ & ANN 1 DAN 2 KARYA RINTIK SEDU - Devi Mutiarani; Sesilia Seli; Agus Wartiningsih (Universitas Tanjungpura, 2022)
This study aims to describe the results of the analysis of the six characteristics of romanticism in the novel Geez & Ann 1 and 2 by Rintik Sedu. The research method used in this study is a descriptive method with a qualitative research form. The approach used in this research is an objective approach. Sources of data in this study.Namely in the form of documents in the form of a novel. The novels used are Gezz & Ann novels 1 and 2 by Rintik Sedu. The technique used in this research is a documentary study technique. The tools used in this study were writing instruments and laptops. The results of this study indicate that romanticism includes a return to nature, moodiness or melancholy, primitivism, sentimentalism, individualism, and exoticism. The materials researcher designed a lesson plan that used the novels Geez & Ann 1 and 2 by Rintik Sedu as a special lesson to achieve KD 3.9 and 4.9 for grade VII SMP.